Eukalyptus Treebank of Written Swedish - Språkbanken Text (University of Gothenburg, 2024)
The Eukalyptus Treebank of Written Swedish is a 100 000 token manually
annotated treebank, consisting of texts from five different genres: novels,
wikipedia, blogs, europarl, and news and community information. The
annotation consists of lemmas, word senses, and parts-of-speech (in part
based on the SUC tagset) and syntactic structures (mainly based on MAMBA and
SAG) which were developed together for the treebank. The Eukalyptus treebank
was developed for evaluation purposes a part of the project Koala - Korps
lingvistiska annotationer, att utveckla en infrastruktur för text-baserad
forskning med högkvalitativa annotationer [Koala – Korp's linguistic
annotations, developing an infrastructure for text-based research with high
quality annotations] funded by Riksbankens Jubileumsfond (2014–2017; nr
In13-0320:1 to Yvonne Adesam et al).

The Eukalyptus Treebank of Written Swedish is a 100 000 token manually
annotated treebank, consisting of texts from five different genres: novels,
wikipedia, blogs, europarl, and news and community information. The
annotation consists of lemmas, word senses, and parts-of-speech (in part
based on the SUC tagset) and syntactic structures (mainly based on MAMBA and
SAG) which were developed together for the treebank. The Eukalyptus treebank
was developed for evaluation purposes a part of the project Koala - Korps
lingvistiska annotationer, att utveckla en infrastruktur för text-baserad
forskning med högkvalitativa annotationer [Koala – Korp's linguistic
annotations, developing an infrastructure for text-based research with high
quality annotations] funded by Riksbankens Jubileumsfond (2014–2017; nr
In13-0320:1 to Yvonne Adesam et al).
Eukalyptus skriven svenska
Keywords: Language Technology (Computational Linguistics); treebank; contemporary; corpus; Natural Language Processing; Språkbehandling och datorlingvistik